2009
DOI: 10.1073/pnas.0910144107
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of factor IXa recognition by heparin-activated antithrombin revealed by a 1.7-Å structure of the ternary complex

Abstract: Factor (f) IXa is a critical enzyme for the formation of stable blood clots, and its deficiency results in hemophilia. The enzyme functions at the confluence of the intrinsic and extrinsic pathways by binding to fVIIIa and rapidly generating fXa. In spite of its importance, little is known about how fIXa recognizes its cofactor, its substrate, or its only known inhibitor, antithrombin (AT). However, it is clear that fIXa requires extensive exosite interactions to present substrates for efficient cleavage. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
67
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(78 citation statements)
references
References 45 publications
(48 reference statements)
5
67
0
Order By: Relevance
“…(ii) How has a likely successful attempt to induce helix D extension failed to result in RCL hinge expulsion and large increase in heparin affinity (true for both hD(131-136) and hD(132-136))? Although one can only speculate at this point as to how this decoupling might have occurred and why these two variants are not identical to H5-bound WT, it is noteworthy that, although the side chain of Lys-133 points into solution in heparin-free antithrombin (32), it points inward to make a salt bridge with Glu-414 in all H5-bound antithrombin complexes examined in which the RCL hinge has been expelled, including antithrombin-H5 (32), antithrombin-H5-anhydrothrombin (33), antithrombin-H5-S195A factor Xa (30), and antithrombin-H5-S195A factor IXa (31). In these complexes the lysine side chain is further flanked by another acidic residue (Asp-278).…”
Section: Discussionmentioning
confidence: 99%
“…(ii) How has a likely successful attempt to induce helix D extension failed to result in RCL hinge expulsion and large increase in heparin affinity (true for both hD(131-136) and hD(132-136))? Although one can only speculate at this point as to how this decoupling might have occurred and why these two variants are not identical to H5-bound WT, it is noteworthy that, although the side chain of Lys-133 points into solution in heparin-free antithrombin (32), it points inward to make a salt bridge with Glu-414 in all H5-bound antithrombin complexes examined in which the RCL hinge has been expelled, including antithrombin-H5 (32), antithrombin-H5-anhydrothrombin (33), antithrombin-H5-S195A factor Xa (30), and antithrombin-H5-S195A factor IXa (31). In these complexes the lysine side chain is further flanked by another acidic residue (Asp-278).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the RCL P14 residuevated state. Mutagenesis studies (8,9) and x-ray structures of heparin pentasaccharide-activated antithrombin complexes with catalytically disabled factor Xa (10) and factor IXa (11) have shown that allosteric activation is mediated by a common exosite outside the RCL whose engagement by RCL-bound factors Xa and IXa augments the protease interaction with the serpin and thereby enhances reactivity. Recent mutagenesis studies have shown that the exosite is accessible to RCL-bound proteases in the native structure despite RCL insertion into sheet A and contributes to the low antithrombin reactivity with these proteases in the native state (12).…”
mentioning
confidence: 99%
“…Similarly, the number of basic amino acids on the surface of activated protein C provides a binding site for heparin and HS (27). Moreover, structural studies on factor IX or factor X indicate that these proteins interact with heparin via positively charged surfaces homologous to the heparin binding site described in thrombin (28,29). Interestingly, the study of FXII architecture reveals the presence of an electropositive path on the protein surface formed by the fibronectin type II domain and the epidermal growth factorlike region on the protein N terminus (30).…”
Section: Discussionmentioning
confidence: 99%